2021
DOI: 10.3390/ijms222212495
|View full text |Cite
|
Sign up to set email alerts
|

Azoxystrobin Impairs Neuronal Migration and Induces ROS Dependent Apoptosis in Cortical Neurons

Abstract: Fungicides often cause genotoxic stress and neurodevelopmental disorders such as autism (ASD). Fungicide-azoxystrobin (AZOX) showed acute and chronic toxicity to various organisms, and remained a concern for ill effects in developing neurons. We evaluated the neurotoxicity of AZOX in developing mouse brains, and observed prenatal exposure to AZOX reduced neuronal viability, neurite outgrowth, and cortical migration process in developing brains. The 50% inhibitory concentration (IC50) of AZOX for acute (24 h) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…7 An in vitro study showed that AZO could impair neuronal migration and induce ROS-dependent apoptosis in cortical neurons. 8 In conclusion, AZO residues are increasingly recognized as a global public health issue.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 An in vitro study showed that AZO could impair neuronal migration and induce ROS-dependent apoptosis in cortical neurons. 8 In conclusion, AZO residues are increasingly recognized as a global public health issue.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, the effect of AZO on oocyte maturation was first examined by evaluating the GVBD and PBE rates. Previous studies have shown that AZO at 1 μM was sufficient to induce changes in transcriptional activity, while 5-10 μM could result in reactive oxygen species accumulation in primary neuronal cells (Pearson et al, 2016;Simon et al, 2019;Kang et al, 2021). Moreover, AZO at micromolar concentrations (1-3 μM) has been shown to modify membrane ion permeability in thymocytes (Imura et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence suggests that AZO has the potential to induce developmental toxicity in animals. For instance, AZO has been reported to impair cortical migration by increasing reactive oxygen species (ROS) levels and inducing mitochondrial deactivation in mouse embryos (Kang et al, 2021). Also, parental exposure to AZO in zebrafish may cause mortality and developmental malformations in their F1 offspring (Cao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…And no reproductive or offspring effects were seen in the 2-generation rat reproduction study. However, it was shown that AZOX reduced neuronal viability, neurite outgrowth, and cortical migration process in developing brains ( Kang et al, 2021 ). Studies have shown that AZOX can target mitochondria and inhibit the electron transport of the oxidative phosphorylation process, leading to reduced cellular energy ( Huttemann et al, 2007 ; Shi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relevant study has shown that AZOX inhibits the viability of human esophageal cancer cells KYSE-150 and induces mitochondrial pathway of apoptosis ( Shi et al, 2017 ). And AZOX inhibits neuronal migration and induces apoptosis in cortical neurons ( Kang et al, 2021 ). In our previous study, we found that AZOX inhibited oral carcinogenesis by specifically targeting mitochondrial complex III, leading to ROS accumulation, MMP reduction and apoptosis.…”
Section: Introductionmentioning
confidence: 99%